A Soproni Tájvédelmi Körzet túraútvonalainak geoinformatikai vizsgálata - Sajtos Márton (2019)
Examinaton the hiking trails of Sopron Landscape Protection Area. The goal of the thesis was the examination of hiking trails in the territory of Sopron Landscape Protection Area. I studied the changes of trails using different versions of tourist maps. Furthermore, I examined the connection between the trails and the natural treasures, and what sorts of problems can cause the dense trail network for the landscape protection area. Using the hiking trails, I made suggestions for trails, and created maps for these paths.